AN OVERVIEW OF THE VI EULAR SCIENTIFIC EDUCATIONAL COURSE DEDICATED TO SYSTEMIC LUPUS ERYTHEMATOSUS (PISA, ITALY, SEPTEMBER 1–6, 2013) - T. A. Panafidina (Научно-практическая ревматология)
The article presents an overview of the lectures and workshops of the VI scientific educational course by the European League against Rheumatism (EULAR) dedicated to systemic lupus erythematosus (SLE), which was held in Pisa, Italy, in early September 2013. The course aims were to train young practicing rheumatologists to make early diagnosis and provide timely and adequate treatment with allowance for the current concepts of SLE etiopathogenesis; the use of the EULAR recommendations and classification criteria; and analysis of complex clinical cases. The main issues of this course included lesion of the nervous system in SLE, lupus nephritis, therapy with traditional and biological response modifiers, management of pregnancy in SLE patients, the need for standardization of the methods for the diagnosis and treatment of these conditions.